A survey of necrophagous blowflies (Diptera: Oestroidea) in the Amazonas-Negro interfluvial region (Brazilian Amazon) (2016)
The fauna of blowflies (Calliphoridae and Mesembrinellidae) in three localities of primary Amazon forest coverage in the Amazonas-Negro interfluvial region was assessed. A total of 5066 blowflies were col- lected, with Chloroprocta idiodea being the most abundant species (66.3%). A difference in species richness between the localities ZF2 and Novo Airão was observed. Comparison among sampled sites revealed no considerable variation in fauna composition, exceptfor the species Eumesembrinella benoisti(Séguy 1925) and Hemilucilia sp., whose occurrence was observed only in a single locality. Apparently, Amazon rivers are not efficient geographical barriers to influence the current composition of necrophagous blowfly assemblages. Also, most of the blowfly species did not show a noticeable specificity for any specific forest among the interfluvial areas of the ombrophilous forest. Finally, an updated checklist of necrophagous blowfly species of the Amazonas state in Brazil is presented.